Supraglacial geomorphology of Companion Glacier, central Himalaya: evolution, controls and consequences - Garg, Purushottam Kumar; Mehta, Manish; Shukla, Aparna; Chauhan, Pankaj; Kesarwani, Kapil; Mukherjee, Sandipan (Frontiers in Earth Science, 2023)
Supraglacial debris cover greatly influences glacier dynamics. The present study combines field and remote sensing observations acquired between 2000 and 2020 to understand debris characteristics, area and terminus changes, surface velocity, and mass balance of the Companion Glacier, Central Himalaya, along with a systematic investigation of its supraglacial morphology. According to field observations, the glacier’s lower ablation zone has very coarse and thick debris (1-3 m). Owing to thick debris and consequent protected margins, the glacier could maintain its geometry during the study (2000-2020) showing much less area loss (0.07 ±0.1% a−1) and terminus retreat (1.2 ±1.9 m a−1) than other glaciers in the study region. The average mass balance (−0.12 ±0.1 m w.e. a−1; 2000-2020) was also less negative than the regional trend. Interestingly, in contrast to widespread regional velocity reduction, Companion's average velocity increased (by 21%) from 6.97 ±3.4 (2000/01) to 8.45 ±2.1 m a−1 (2019/20). Further, to investigate supraglacial morphology, the glacier ablation zone is divided into five zones (Zone-I to V; snout-to-up glacier) based on 100 m altitude bins. Analysis reveals that stagnation prevails over Zone-I to Zone-III, where despite slight acceleration, the velocity remains <~8 m a−1. Zone-V is quite active (12.87 ±2.1 m a−1) and has accelerated during the study. Thus, Zone-IV with stable velocity, is sandwiched between fast-moving Zone-V and slow-moving Zone-III, which led to bulging and development of mounds. Debris slides down these mounds exposing the top portion for direct melting and the meltwater accumulates behind the mounds forming small ponds. Thus, as a consequence of changing morphology, a new ablation mechanism in the form of spot-melting has dominated Zone-IV, leading to the highest negative mass balance here (−0.5 ±0.1 m w.e. a−1). The changing snout and supraglacial morphology, active mound-top’s melting and formation of ponds likely promote relatively higher glacier wastage in the future.